Pengaturan Tentang Saksi Keluarga Pada Perkara Perceraian Akibat Perselisihan Secara Terus-Menerus - Ida Ayu Tri Astuti Purwasari; I Ketut Mertha (University of Udayana, 2022)
This study aims to find out and briefly about the Arrangement of Family Witnesses in Divorce Cases Due to Continuous Disputes. This study uses normative legal methods. The arrangement of family witnesses in providing information in divorce cases due to continuous disputes, namely a conflict of norms between Article 22 paragraph (2) of the Marriage Regulation and Article 1910 of the Civil Code. Based on the principle of lex superior derogat legi inferiori in resolving the problem of conflicting norms between Article 22 paragraph (2) of the Marriage Regulation and Article 1910 of the Civil Code, the basis will be Article 1910 of the Civil Code, which determines that the family is considered incompetent in giving testimony in case. The legal consequences of divorce in Indonesia on property during marriage, if you pay attention to the explanation of Article 37 officially do not provide positive legal uniformity on how to divide joint property in the event of a divorce. Furthermore, the way of dividing joint property in the provisions of the law and submitting it to the law that lives in the community where the divorce and household are located. If we return to the explanation of Article 37, then the regulation has shown a description of how to divide joint property, namely